Strategies and applications of antibacterial surface-modified biomaterials - Qianwei Su; Yunyun Xue; Chuyao Wang; Qirong Zhou; Yu Zhao; Jiacan Su; Baoku Zhu (Bioactive Materials, 2025)
Bacterial infections and biofilm-associated antibiotic resistance continue to pose significant challenges in biomedical applications, often resulting in device-related complications and therapeutic failures. To address these concerns, the development of antibacterial surface-engineered biomaterials has become a major research focus, offering localized, non-systemic strategies to combat microbial contamination. This review provides a comprehensive overview of recent advances in antibacterial surfaces, with a focus on their mechanisms of action, design principles, and functional performance. Strategies are discussed within the widely recognized categories of active, passive, and hybrid systems. Active surfaces function through agent release or contact-mediated killing, while passive surfaces inhibit bacterial adhesion by modulating surface topography or chemistry. Hybrid systems integrate both mechanisms to achieve synergistic effects. The review also highlights current and emerging applications in medical implants, wound care, and hygienic textiles. Finally, key limitations and future opportunities are critically examined, offering insights into the rational design and clinical translation of next-generation antibacterial biomaterials.